A predictive model of the tensile strength of twisted carbon nanotube yarns. (29th November 2016) - Jeon, Seung-Yeol; Jang, Jinhyeok; Koo, Bon-Woong; Kim, Young-Woon; Yu, Woong-Ryeol
Abstract: Due to the outstanding mechanical properties of individual carbon nanotubes (CNTs) at the nanoscale, CNT yarns are expected to demonstrate high strength at the macroscale. In this study, a predictable model was developed to predict the tensile strength of twisted CNT yarns. First, the failure mechanism of twisted CNT yarns was investigated using in situ tensile tests and ex situ observations. It was revealed that CNT bundles, which are groups of CNTs that are tightly bound together, formed during tensile loading, leaving some voids around the bundles. Failure of the CNT yarns occurred as the CNT bundles were pulled out of the yarns. Two stresses that determined the tensile strength of the CNT yarns were identified: interfacial shear and frictional stresses originating from van der Waals interactions, and the lateral pressure generated by the twisted yarn structure. Molecular dynamics and yarn mechanics were used to calculate these two stresses. Finally, the tensile strength of CNT yarns was predicted and compared with experimental data, showing reasonable agreement.